Job-Search Activities, Job-Seeking Barriers, and Work Experiences of Transition-Age Youths With Visual Impairments. (November 2021) - Cmar, Jennifer L.; Steverson, Anne
Introduction: The purpose of this study was to describe the job-seeking and work experiences of transition-age youths with visual impairments.Methods: We analyzed follow-up data from a quasi-experimental study of a job-search intervention conducted from 2016 to 2019. Participants were 88 youths with visual impairments from three states; approximately half received the job-search intervention, and the other half served as a comparison group. Measures included job-search activities and outcomes, job-seeking barriers, volunteer and work experiences, and parental support for job-seeking.Results: Commonly reported job-search activities were preparing or revising resumes, talking to people about jobs, submitting applications, and submitting resumes, but most participants performed these activities infrequently. Many job-seekers encountered barriers during their job search, and few searches resulted in paid employment. Participants generally reported moderate levels of preparation to handle job-seeking barriers and parental support for job-seeking. Intervention and comparison participants had similar results on most measures, with few exceptions.Discussion: When youths actively search for a job but do not find one, their motivation to continue job-seeking may be reduced, particularly if their preparedness to overcome job-seeking barriers is low. Although many participants had some engagement in volunteer or work activities, short-term work experiences were the most common—and perhaps most misunderstood—work activity.Implications for practitioners: Youths with visual impairments may benefit from feedback on their job-seeking approach, application materials, and interview skills so they can make changes and determine how to focus or refocus their efforts. In addition to offering feedback, service providers can provide ongoing support to youth job-seekers and encourage them to persist in their job search. Explicit discussions about different types of work activities may help transition-age youths understand how short-term work experiences differ from paid jobs.